QUANTITATIVE AND QUALITATIVE COMPARISONS BETWEEN NECESSARY METHODS, APPLICABLE TO WELDING STEEL 13CrMo4-5, TO ESTABLISH THE PREHEATING TEMPERATURE - Dumitru Titi CICIC; Corneliu RONTESCU; Oana Roxana CHIVU; Stefan Constantin PETRICEANU (Fiabilitate şi Durabilitate)
The paper presents and compares a series of standardized and non-standardized methods for determining the pre-heating temperature (Tpr) applied to reduce or eliminate negative effects resulting from the use of the welding process, such as cold cracking. The results of quantitative and qualitative comparisons of the various Tpr calculating/setting methodologies are presented, but the preheat temperature values obtained for a case study referring to 13CrMo4-5 steel welding, a heat-resistant steel used in the case of the pressure-generating products in the energy industry.